Digital Productive Waqf: Contextualization of Sharia Economic Law in Indonesia - Wahidah Z, Wahidah Z (Abdurrauf Journal of Islamic Studies, 2025)
The digital transformation in waqf management has shifted traditional practices toward a more modern, transparent, and participatory system. While digitalization provides significant opportunities for optimizing productive waqf, current regulations remain conventional and have yet to fully accommodate the needs of the digital era. This study aims to analyze the role of digitalization in developing productive waqf in Indonesia and to evaluate the responsiveness of Islamic economic law regulations to these transformations. This research employs a qualitative approach using literature review and normative analysis. Data were obtained from a review of waqf regulations, DSN-MUI fatwas, and both national and international academic literature on waqf digitalization. Digitalization offers substantial opportunities to enhance transparency, accountability, and public participation in productive waqf. However, Islamic economic law regulations in Indonesia are not yet fully responsive to emerging issues such as digital data protection, transaction security, and technology-based governance. Differences in fatwa interpretation also present challenges in implementing digital waqf. Digitalization of productive waqf has great potential to support the economic empowerment of the Muslim community. Nevertheless, regulatory reforms, stronger roles for supervisory authorities such as BWI, DSN-MUI, and OJK, as well as improved public digital literacy, are required to maximize its benefits. This article contributes a new perspective on the urgency of strengthening the legal framework and governance of digital waqf that is adaptive to technological developments, providing both a conceptual foundation for future research and guidance for policy formulation. [Transformasi digital dalam pengelolaan wakaf telah mengubah paradigma tradisional menuju sistem yang lebih modern, transparan, dan partisipatif. Digitalisasi menghadirkan peluang besar bagi optimalisasi wakaf produktif, namun regulasi yang ada masih berbasis konvensional dan belum sepenuhnya mengakomodasi kebutuhan era digital. Penelitian ini bertujuan menganalisis peran digitalisasi dalam pengembangan wakaf produktif di Indonesia serta mengevaluasi responsivitas regulasi hukum ekonomi syariah terhadap perubahan tersebut. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi literatur dan analisis normatif. Data diperoleh melalui telaah terhadap regulasi wakaf, fatwa DSN-MUI, serta literatur akademik nasional dan internasional terkait digitalisasi wakaf. Digitalisasi membuka peluang besar dalam meningkatkan transparansi, akuntabilitas, serta partisipasi masyarakat dalam wakaf produktif. Namun, regulasi hukum ekonomi syariah di Indonesia belum sepenuhnya responsif terhadap isu-isu baru seperti perlindungan data digital, keamanan transaksi, dan tata kelola berbasis teknologi. Perbedaan interpretasi fatwa juga menjadi tantangan dalam implementasi wakaf digital. Digitalisasi wakaf produktif memiliki potensi besar dalam mendukung pembangunan ekonomi umat, tetapi diperlukan pembaruan regulasi, penguatan peran otoritas pengawas seperti BWI, DSN-MUI, dan OJK, serta peningkatan literasi digital masyarakat agar manfaatnya dapat dimaksimalkan. Artikel ini memberikan perspektif baru mengenai urgensi penguatan kerangka hukum dan tata kelola wakaf digital yang adaptif terhadap perkembangan teknologi, serta menawarkan basis konseptual bagi penelitian lanjutan dan perumusan kebijakan.]